Ecofisiologia da germinação de sementes de Clidemia hirta (L.) D. Don (Melastomataceae) - Pereira-Diniz, Sandra Graciele (2003)
Clidemia hirta (L.) D. Don (Melastomataceae) is a pioneer species, invader and damaging, amply distributed in Tropical America. In the area of the biome Cerrado it occurs on the borders of gallery forest, in shaded places, flowering and fruiting practically all year round. It plays an important role in the succession processes of natural glades and in the secondary succession of areas disturbed by the action of man. This work had as its objective to study the pattern of germination of recently-picked Clidemia hirta seeds, occurring in the Ecological Station of Panga, Uberlândia-MG. Seeds were submitted to eight treatments, with six repetitions of 50 seeds each, in entirely casual experimental delineation design, according to the following discrimination: seeds maintained in giberelic acid at 10 μg mL-1 (1); in 100 μg mL-2, under continuous light (2); seeds maintained in KNO3 at 0.2% under continuous light (3) and seeds maintained in distilled water (4) under continuous light; seeds maintained in darkness in giberelic acid at 10 μg mL-1 (5) and at 100 μg mL-2 under continuous light (6); seeds maintained in darkness in KNO3 at 0.2% (7) and seeds maintained in darkness in distilled water (8). The mean radiance was of 37.15 pmol s-1 m-2 and the temperature of 22-23.5 °C. The protrusion of the embryo was considered as the criterion germination. The data were used to calculate the ability of germination, for the mean time, the eoefficient of variation of the mean time, the mean speed and the index of synchronized germination. The data were submitted to normality tests, homogeneity, Kruskal-Wallis, Mann-Whitney, ANOVA and Tukey test. The late germination (mean time between 16 and 22 days), lade of synchronism and prolonged period of germination (taking place between seven and 80 days) mdicates that the seeds present primary dormancy. Potassium nitrate reduced the mean time, mcreased the speed and the synchronic of germination in relation to the other treatments, indicating that it was more effective in breaking dormancy of the seeds in relation to giberelic acid. However, the ability to germinate of these seeds maintained in KNO3 was only 4.5% compared to 33 - 37% in other treatments, which shows that the potassium nitrate provokes an osmotic eflfect on the seeds of this species. The seeds maintained in darkness were not able to germinate and were, therefore, considered fotoblastic. This reinforces the hypothesis that the seeds of Clidemia hirta present Pnmary dormancy related to the tegument, as no substance stimulated the germination of the seeds Maintained in darkness. Dormancy is an important characteristic of these seeds, determining the Access of the species as pioneer, invader and damaging.